2016
DOI: 10.1111/jnc.13510
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid (DHA) prevents corticosterone‐induced changes in astrocyte morphology and function

Abstract: The many functions of astrocytes, such as glutamate recycling and morphological plasticity, enable them to stabilize synapses environment and protect neurons. Little is known about how they adapt to glucocorticoid-induced stress, and even less about the influence of dietary factors. We previously showed that omega-3 polyunsaturated fatty acids (x3PUFA), dietary fats which alleviate stress responses, influence the way astroglia regulate glutamatergic synapses. We have explored the role of docosahexaenoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
2
18
1
Order By: Relevance
“…In contrast, spreading was restricted to the OB ventral and medial parts after fasting for 24 h, while fasting for 48 hr induced no astroglial spreading in any OB region. This may counteract glomerular astroglial spreading, since we and others have shown that corticosterone induces retraction of the astrocyte processes in vitro (Champeil-Potokar et al, 2015) and in vivo (Tynan et al, 2013). Prolonged fasting is stressful, and fasting for 24 hr to 48 hr activates the HPA axis and increases blood corticosterone in rats, depending on strain and age (Dietze, Lees, Fink, Brosda, & Voigt, 2016;Rowland, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, spreading was restricted to the OB ventral and medial parts after fasting for 24 h, while fasting for 48 hr induced no astroglial spreading in any OB region. This may counteract glomerular astroglial spreading, since we and others have shown that corticosterone induces retraction of the astrocyte processes in vitro (Champeil-Potokar et al, 2015) and in vivo (Tynan et al, 2013). Prolonged fasting is stressful, and fasting for 24 hr to 48 hr activates the HPA axis and increases blood corticosterone in rats, depending on strain and age (Dietze, Lees, Fink, Brosda, & Voigt, 2016;Rowland, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The amounts of three specific glial marker proteins, GFAP, glutamateaspartate transporter (GLAST) and glutamine synthetase (GS), were measured by immunoblotting as previously described (Champeil-Potokar, Hennebelle, Latour, Vancassel, & Denis, 2015). OBs were homogenized in radioimmunoprecipitation assay buffer containing antiproteases (protease inhibitor cocktail tablets, Roche Diagnostics, France), assayed for protein contents, diluted in sample buffer, separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (4-15% gradient Tris-HCl-polyacrilamide gels, BioRad, France) and transferred to polyvinylidene fluoride membranes.…”
Section: Western Blottingmentioning
confidence: 99%
“…Restriction of ω‐3 PUFA levels in male mice from pregnancy onset until 4 months of age resulted in greater GFAP + coverage in response to traumatic brain injury, an effect that was diminished when ω‐3 levels were restored (Desai et al, ). Treatment of cultured astrocytes with DHA was able to prevent a CORT‐induced stress response as measured by increased glutamate uptake, increased GS levels, and altered GFAP cytoskeletal morphology (Champeil‐Potokar, Hennebelle, Latour, Vancassel, & Denis, ). Similarly, adolescent restriction of tryptophan, an essential amino acid crucial for protein biosynthesis during development, results in astrocyte activation as shown by GFAP cytoskeletal hypertrophy in the hippocampus and amygdala immediately following tryptophan restriction (Zhang, Corona‐Morales, Vega‐González, García‐Estrada, & Escobar, ).…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 99%
“…Vancassel, & Denis, 2016). Similarly, adolescent restriction of tryptophan, an essential amino acid crucial for protein biosynthesis during development, results in astrocyte activation as shown by GFAP cytoskeletal hypertrophy in the hippocampus and amygdala immediately…”
mentioning
confidence: 99%
“…In vitro, glucocorticoid treatment induces rapid increases in astrocyte Ca 2+ signalling suggestive of an activation of non‐genomic pathways downstream of glucocorticoid receptors. Glucocorticoid treatment of astrocytes in culture also enhances neuropeptide (ie, atrial natriuretic peptide) release from astrocytes, promotes glutamate recycling, and leads to increases in GFAP‐immunoreactivity and rearrangement of F‐actin fibres, indicative of cellular stress . By contrast, chronic treatment of primary astrocytes in culture with glucocorticoids reduces cellular proliferation and glucocorticoid receptor expression .…”
Section: Astrocytes and The Neuroendocrine Regulation Of The Stress Rmentioning
confidence: 99%